1985
DOI: 10.1111/j.1464-5491.1985.tb00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Glucose Responses to Glucose, Sucrose, and Honey in Patients with Diabetes Mellitus: An Analysis of Glycaemic and Peak Incremental Indices

Abstract: We have studied the hyperglycaemic effect of the carbohydrate of glucose, sucrose, and honey equivalent to 20 g in twelve normal volunteers, eight patients with insulin-dependent diabetes mellitus (IDDM), and six patients with non-insulin-dependent diabetes mellitus (NIDDM). Honey produced an attenuated postprandial glycaemic response in normal volunteers (vs glucose p less than 0.005; vs sucrose p less than 0.05) and IDDMs (vs glucose p less than 0.005; vs sucrose p less than 0.05). The glycaemic index (GI) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 8 publications
1
32
0
Order By: Relevance
“…Nevertheless, active preoperative carbohydrate preservation has been shown to result in improvement of postoperative metabolism and reduction in the occurrence of postoperative insulin resistance. 28,29 Compared with GFSM or apple juice, honey had a gentler effect on plasma glucose and insulin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, active preoperative carbohydrate preservation has been shown to result in improvement of postoperative metabolism and reduction in the occurrence of postoperative insulin resistance. 28,29 Compared with GFSM or apple juice, honey had a gentler effect on plasma glucose and insulin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…For decades, there has been interest in determining the effects of honey intake on glucose regulation disorders, and controversial results have been obtained. On the one hand, it has been considered that honey consumption by diabetics is pointless because it contains a considerable proportion of sugars (White, 1978;Moreira and De Maria, 2001), while on the other hand, some research has produced interesting results positioning honey as a potential nutritional supplement for subjects with disorders of glucose homeostasis (Bornet et al, 1985;Samanta et al, 1985;Katsilambros et al, 1988;Shambaugh et al, 1990;Al-Waili, 2004;Agrawal et al, 2007;Ahmad et al, 2008).…”
Section: Effects On Glycemic Regulationmentioning
confidence: 99%
“…However, recently published research has suggested that floral sources of the honey species may influence GI and that some honey varieties show a lower GI than do others (Samanta et al, 1985;Foster-Powell et al, 2002;Henry et al, 2005;Ischayek and Kern, 2006).…”
mentioning
confidence: 99%